Predictors of improvement in semen parameters after varicocelectomy for male subfertility: A prospective study - Shabana, Waleed; Teleb, Mohamed; Dawod, Tamer; Elsayed, Ehab; Desoky, Esam; Shahin, Ashraf; Eladl, Mahmoud; Sorour, Waleed (Canadian Urological Association Journal, 2015)
Introduction: We aim to predict results of varicocelectomy on sperm density and progressive motility using preoperative clinical, laboratory and radiological data and to propose cut-off values for significant parameters. Methods: This prospective study was carried out between July 2011 and June 2014. We included 123 patients in our study. They were diagnosed with primary infertility with varicocele, were scheduled for varicocelectomy, and completed their follow-up. We excluded patients with azoospermia, total necrospermia, recurrent varicocele, and pituitary hormonal abnormalities. Varicocele was diagnosed and graded by physical examination and colour Doppler ultrasound. Semen analyses were completed preoperatively and 6 months postoperatively. Microscopic subinguinal varicocelectomy was done in all cases. Patient demographics, pre- and postoperative clinical data (varicocele grade and semen parameters) were statistically analyzed. Results: The mean ± standard deviation of age, body mass index, and subfertility duration was 28.3 ± 7.4 years, 29.1 ± 2.7 kg/m2, and 21.9 ± 7.1 months, respectively. About 53% of our patients (n = 66) had bilateral varicocele, and unilateral disease was found in the other 57 (46.3%) cases. Varicocele grade I was diagnosed in 42 (34.1%) patients, while the other 81 (65.9%) patients had grade II or III. Higher grades of varicocele, preoperative total testosterone level, sperm density, and progressive motility had a statistically significant impact on the outcome of varicocelectomy in univariate testing. Multivariate logistic analysis revealed that grade of preoperative varicocele (95% confidence interval [CI] 5.6–6.3, p = 0.007) and sperm density (95% CI 2.7–1.6, p = 0.0035), and progressive motility (95% CI 1.1–2.3, p = 0.0123) are independent predictors of semen parameters improvement after varicocelectomy. Conclusion: The grade of the varicocele, sperm density, and progressive motility are major predictors of outcome in varicocelectomy. Cut-off values of >8 million/mL and >18% for sperm density and progressive motility, respectively, in men with varicocele grade II or III, indicate a successful outcome.